Historical Memory versus Communist Identity - Saueauk, Meelis (2014)
This collection consists of articles on the subjects addressed by the research conference “The Shaping of Identity and Personality under Communist Rule: History in the Service of Totalitarian Regimes in Eastern Europe”, held in Tallinn, Estonia, on 9–10 June 2011 and arranged by the Estonian Institute of Historical Memory Foundation and the Unitas Foundation. The organisers of the conference intended to describe, analyse and explain the state policies and activities used in Eastern Europe for shaping the Communist identity and personality by means of manipulating the historical consciousness, and the efficiency of those policies and activities, proceeding from the official historical approaches of the former Eastern bloc. Ideologically mutated history was the important component of the official, Communist identity. The artificial official history and the new historical identity it forced upon the population aspired to establish the sole possible truth by means of half-truths. Probably the most important thread that comes through every article in this collection is the conflict between the official, communist identity and the nation's historical memory, and its consequences.